Allan McCollum - Anastas, Rhea 1969- (JRP Ringier, 2012)
Since the late 1970s, Allan McCollum (b. 1944, Los Angeles, lives in New York) has addressed the production, distribution, acquisition, display, and reading of the artwork. His constant use of strategies of multiplication, his examination of the museum as a discursive agent, and his recurrent interest in notions of display, as well as his attempt to find a generic form for any purpose, were entirely reconfigured by this displacement of context. Working with regional museums, heterogeneous audiences, and references ranging from palaeontology to mineralogy, McCollum has built a very strong and intriguing body of works that has remained, in large part, unknown to (or at least unseen by) the art world